Overview of the evolutionary history and the role in citric acid production of alternative oxidase - Szojka, Anikó (Acta Agraria Debreceniensis, 2013)
All organisms are exposed to countless environmental effects, which influence in a disadvantageous way their life processes. They continuously adapt to the changing conditions and respond to the stress impacts by defence mechanisms. Through different signal transduction pathways they are able to increase or decrease the expression of their genes and consequently modify their metabolic processes. My interest focuses on alternative oxidase (AOX) enzyme whose expression is often increased under biotic and abiotic stress. The so far proven and putative functions of the AOX play a role in the ability of organisms to adapt to different conditions, such as heavy metals accumulation, pathogenic infection, oxidative stress and lack of oxygen or nutrients.AOX is a member of the di-iron carboxylate protein family. Members of the di-iron carboxylate protein family are present in all kingdoms of life. They are considered to have ancient origin. It is believed that their sulfide-resistant and oxygen-reducing ability played a role in the survival of organisms during the transition between the anaerobic and the aerobic world. It is assumed that the AOX arose in eukaryotes through a primary endosymbiotic event, and this event made possible the development of mitochondria. Afterwords, vertical inheritance, and secondary and tertiary endosimbiotic events led to its spread among eukaryotes. It is assumed that bacteria obtained AOX by horizontal gene transfer from plants.AOX-catalyzed alternative respiration plays an important role in the operation of energy-producing and biosynthesizing system of microorganisms. In these cases, the regeneration of reduced cofactors is an essential condition, and therefore may be rate-limiting for biotechnological processes, including the citric acid production.